The Implementation of Interactive Planning To Propose Strategic Solution For Tourism Promotion - Rikantini Widiyanti; Narendra Radi Muhammad (Journal of Tourism Sustainability, 2021)
Information distribution through digital platform helps business owner improve their performance in promotion to broader market without geographical barriers. Unfortunately, the use of digital platforms still does not meets success performance as marketing tools. Information in digital platform has not provided the update and accurate information of destination. Moreover, it effects in rising potential tourist awareness and experience satisfaction. The purpose of this paper is to investigate the promotional problem that effects tourist awareness of tourism destination and recommend the strategic solution to improve performance by concerning tourism stakeholder involvement. This study introduces creative problem solving as an approach to identify probability source of difficulties and recommend strategy solution of problems faced. Interactive Planning (IP) is proposed to investigate the problem and find the strategic recommendation related to destination promotional activities. A comprehensive strategic based study will enhance strength to previous study. Interview and Focus Group Discussion conducted to fill the information needed qualitatively. Wide-ranging roles by diverse backgrounds from five elements Penta Helix (government, academic, media, business, and community) able to strengthen promotion in integrated information manner. The proposed result that might be able to give effect positive in the long term in promotion of tourism sector.